Comparative Effects of Argumentation and Laboratory Experiments on Metacognition, Attitudes, and Science Process Skills of Primary School Children - Jale Kalemkuş; Şule Bayraktar; Sabahattin Çiftçi (Journal of Science Learning, 2021)
The purpose of this study is to investigate and compare the effects of laboratory experiments and argumentation-based science teaching on science process skills, metacognitive awareness levels, and attitudes towards science of 4th-grade elementary school students. In this study conducted according to the quantitative research method, a pre-test and post-test quasi-experimental design were used with two experimental groups and a control group. Students from three classes of an elementary school participated in the study (N = 98). "Science Process Skills Test", "What Do I Really Think about Science Scale", and "Metacognitive Awareness Scale" were employed to collect data for the research. The study results showed that the science process skills of the 4th-grade students improved significantly in both experimental groups, which were taught by employing experiments and argumentation. Students' metacognitive awareness levels and attitudes towards science developed in all three groups.  However, it was observed that the development was higher in the groups in which science teaching based on experiments and argumentation-based science teaching was performed, compared to the control group.